2017
DOI: 10.3851/imp3238
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Combination Therapy for Cytomegalovirus Infection in High-Risk Infants

Abstract: Combination GCV + FOS therapy may be a safe alternative to monotherapy in high-risk infants, especially those who are pre-transplant with primary immune deficiency syndromes and high viral loads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In our retrospective study, the use of several drugs in different national reference units reflects the clinicians’ difficulties to treat CMV disease in immunocompromised patients. Vora et al have recently suggested that combined antiviral therapy could be a safe option for high-risk children with primary immunodeficiencies in pre-transplantation settings, especially for those with high viral loads [ 28 ]. Although these data have to be considered with caution and further studies are needed, dual therapy could be an option in infants with PID and severe CMV disease without viral load control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our retrospective study, the use of several drugs in different national reference units reflects the clinicians’ difficulties to treat CMV disease in immunocompromised patients. Vora et al have recently suggested that combined antiviral therapy could be a safe option for high-risk children with primary immunodeficiencies in pre-transplantation settings, especially for those with high viral loads [ 28 ]. Although these data have to be considered with caution and further studies are needed, dual therapy could be an option in infants with PID and severe CMV disease without viral load control.…”
Section: Discussionmentioning
confidence: 99%
“…Adoptive immunotherapy with virus-specific T-cells appears to have limited efficacy for treating disseminated cytomegalovirus infections in pre-transplantation settings [ 19 , 22 ]. Given that the presence of active cytomegalovirus infection adversely affects survival [ 1 , 6 , 28 ], adoptive immunotherapy could be administered as a rapid salvage therapy to reduce viremia until immunity is reestablished with an HSCT [ 19 , 22 ]. Lastly, adjuvant therapy with intravenous immunoglobulin or with cytomegalovirus-specific hyperimmune globulin may be considered in cases of severe disease associated with hypogammaglobulinemia [ 6 ], although its effect remains controversial [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, antiviral prophylaxis is established with acyclovir or valacyclovir at least up to one year after CAR-T infusion, or until a CD4+ T lymphocyte level greater than 0.2 x 10 9 /L is documented ( 134 ). In paediatrics, nonspecific immunoglobulins are also frequently used to maintain total IgG levels above 0.4 g/L ( 135 ). With respect to monitoring, the EBMT guidelines recommend that PCR be performed when clinically indicated ( 133 ).…”
Section: In the Haematological Settingmentioning
confidence: 99%
“…Viruses were able to interfere with the reproductive function in both sexes. The CMV virus is transmission by close contacts among infected subjects, via such as blood or blood products, congenital, sexual intercourse (8). Infections for congenital HCMV are mostly noted as causes of hearing loss and mental retardation; latent CMV infections can be activated in immune compromised patients, e.g.…”
Section: Introductionmentioning
confidence: 99%